Dexmedetomidine Adjuvant in Awake Intubation as Difficult Airway Management for Submandibular Abscess with Mediastinum Infiltration - Ardana Tri Arianto; Sigit Prastya Utama; Asaduddien Faras (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background: Maintaining a secure airway in difficult airway settings is important due to morbidity and mortality. Conventional intubation relies on benzodiazepines, opioids, and propofol which have a respiratory depression effect. Dexmedetomidine has a minimal to no central respiratory depression effect. A submandibular abscess can result in laryngeal edema which narrows or occludes the airway.Case Ilustration: A 65-year-old male complained of difficulty breathing and shortness of breath accompanied by neck and right jaw pain that radiated to the right cheek. The patient also complained of a salty taste every time the patient swallows. Obtained blood pressure 112/73 mmHg on norepinephrine support syringe pump 0.1 mcg/kg/minute (5.4 cc/hour), pulse rate 120 bpm, respiratory rate 32 times per minute with the help of respiratory muscles. The patient’s temperature was 36.7oC. The patient’s initial Glasgow Coma Scale was E3V5M6. Difficult airway was observed due to submandibular mass, 1-2 finger mouth opening, trismus, mallampati was difficult to evaluate, limited neck motion due to pain, and missing teeth. Imaging showed a soft tissue mass in the neck region. The patient underwent awake intubation using a video laryngoscope and Nasoendotracheal tube number 6.5 was installed with 70 mcg of dexmedetomidine syringe pump in 10 minutes (with pump rate of 105 ml per hour) and lidocaine mouth rinse. The intubation process went smoothly and the patient was admitted to the Intensive Care Unit for further monitoring.Conclusion: Management of difficult airway settings is important due to morbidity and mortality. The use of dexmedetomidine is considered safe and effective in securing the airway in patients with difficult airway.